Cognitive Development of Elementary School Children in Developing Critical Thinking Ability and Understanding Mathematical Concepts - Oktaviani, Maya; Dwihapsari, Kartika; Islami, Mutiara Nur; Dewi, Nadia Puspa; Fadhilah, Rahil Nurul; Palupi, Zahra Dinda (International Education Trend Issues, 2023)
This study aims to determine students' cognitive development in developing critical thinking skills and understanding mathematical concepts at the elementary school level. This study uses qualitative methods with convenience sampling techniques. The researcher collected the data through interviews with six elementary school students from grades 3 to 5 on May 2023. They are inhabitants of Tegal Gundil, Bogor. Some problems identified include the inability to answer random questions, inappropriate questions and answers, disobedience in understanding the teacher's explanation, and external factors hindering elementary school children's cognitive development. Based on these problems, this study found that cognitive development is essential in developing critical thinking skills and understanding mathematical concepts in elementary school-age children. Suggestions include using an inclusive learning approach, adjusting questions and answers, increasing the ability to understand teacher explanations, and collaboration between schools, parents and the community. With the right approach and adequate attention, students can improve their cognitive development by developing critical thinking skills and understanding mathematical concepts.